Reverse ultrasound-assisted emulsification-microextraction of macrolides from chicken fat followed by electrophoretic determination - Lorenzetti, Anabela Silvana (2019)
A new microextraction methodology, called reverse ultrasound-assisted emulsification-microextraction (R-USAEME) was developed to extract Tilmicosin (TILM) and Tylosin (TYL) from chicken fat samples, prior to their determination by capillary electrophoresis with UV-detection. The R-USAEME was based on the use of an aqueous ionic liquid ([Bmim]Cl) solution with sodium tartrate and sodium phosphate as extractant, applying an ultrasound probe (91 W; 7.5 min). A good linearity was obtained in a range from 35 to 200 μg kg−1 with relative standard deviations (RSDs) lower than 13% using matrix-matched calibration on five chicken fat samples. The quantification limits (LOQs), ranged from 17.4 to 55.0 μg kg−1 and from 22.1 to 47.0 μg kg−1 for TILM and TYL respectively. The obtained recoveries were between 73 and 117%. The analytical parameters clearly showed the applicability of the method for the extraction and quantification of macrolides in this complex biological sample.